2015
DOI: 10.4103/0972-5229.152756
|View full text |Cite
|
Sign up to set email alerts
|

Mortality patterns among critically ill children in a Pediatric Intensive Care Unit of a developing country

Abstract: Background and Aim:Advances in biomedical technology have made medical treatment to be continued beyond a point, at which it does not confer an advantage but may increase the suffering of patients. In such cases, continuation of care may not always be useful, and this has given rise to the concept of limitation of life-sustaining treatment. Our aim was to study mortality patterns over a 6-year period in a Pediatric Intensive Care Unit (PICU) in a developing country and to compare the results with published dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
3
28
1
2
Order By: Relevance
“…Similar to previous reports, the majority of deaths in the accompanying study[ 1 ] occurred following limitation of life-sustaining treatments (including “do not resuscitate” orders and “withdrawal of life-support treatment”). [ 3 ] The reader is left to interpret the meaning of “life-support treatment.” This could include any or all of nutritional support, antibiotic treatment, mechanical ventilation, inotropes, fluid therapy, etc.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Similar to previous reports, the majority of deaths in the accompanying study[ 1 ] occurred following limitation of life-sustaining treatments (including “do not resuscitate” orders and “withdrawal of life-support treatment”). [ 3 ] The reader is left to interpret the meaning of “life-support treatment.” This could include any or all of nutritional support, antibiotic treatment, mechanical ventilation, inotropes, fluid therapy, etc.…”
supporting
confidence: 84%
“…present a report on the mortality patterns in Pediatric Intensive Care Units (PICU) in Pakistan, a developing country. [ 1 ] It is difficult to interpret the apparently high mortality rate of almost 13% without the context of average predicted mortality on admission (i.e. standardized mortality rates [SMR]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Similarly, several international studies (from the US, UK, France, and Pakistan) reported that up to 60% of all deaths in PICUs were attributable to DNR orders. [23][24][25][26] Different numbers were reported by Devictor and Nguyen 27 (survey of 12 PICUs from northern Europe and 27 from southern Europe), where the decision to forgo life-sustaining treatment was more often made in PICUs in northern European countries than in southern ones (47% vs 30%, P=0.02). A much higher percentage was reported by Moore et al: 28 74% of deaths in an Australian children's hospital ICU followed the withdrawal and limitation of life-sustaining treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3 Crude mortality rate of children (median age 2.8 years) in a pediatric ICU was shown 12.9%. 28 Ahmed et al 12 showed, crude mortality rate with bloodstream infections in ICU was 38%. .Our study found 26.1% fatal outcome of children from ICU acquired bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%